Menolak Menstrual Taboo dan "Angan-angan" Fiqh Kesetaraan - Mudaris, Hudan (Musawa Jurnal Studi Gender dan Islam, 2007)
Women's issues have always stimulated discussion; and amongst the most debated issues is about menstruation or popularly known as haidh in Islamic literature. This signifies that although menstruation is a routine event for most adult women, it has significant consequencesfor their lives. The debates on the issues of menstruation is heated when they are not only seen within the context of women's reproductive and sexual health, but also put into the theological frame, such as in the event related to religious rituals of prayers and hajj (pilgrimage to the holy land Mecca), in which menstruating women are prohibited to engage with.